State-Space Modeling, Stability Analysis, and Controller Design of Grid-Forming Converters With Distributed Virtual Inertia - Deng , Han; Fang , Jingyang (Frontiers in Energy Research, 2022)
The ever-increasing integration of power converter-coupled renewable energy sources reduces carbon footprints yet weakens power system inertia due to the retirement of synchronous generators. Inertia shortage makes modern power systems sensitive to frequency variations, thereby leading to undesirable load shedding, cascading failures, or even large-scale blackouts. To address the inertia concern, distributed virtual inertia from grid-tied power converters is emerging as an attractive solution. On top of that, there are upcoming standards of grid-tied power converters, such as PV inverters, that require grid formulation. As such, this paper proposes flexible distributed virtual inertia delivered by grid-forming converters without additional energy storage units. It is revealed that virtual inertia control may possibly cause stability problems. Through the derived state-space model and sensitivity analysis, the mechanism of instability is disclosed. Although droop control may stabilize converters, it inevitably necessitates extra energy storage, and is hence not cost-effective. Instead, a lead compensator, together with its design procedure, is proposed. Finally, simulation and experimental results validate the correctness and effectiveness of the proposed model and compensator. Moreover, the results demonstrate that the proposed grid-forming converters allow significant improvements in inertia and frequency regulation.